'No matter what the cost': A qualitative study of the financial costs faced by family and whānau caregivers within a palliative care context. (June 2015) - Gott, Merryn; Allen, Ruth; Moeke-Maxwell, Tess; Gardiner, Clare; Robinson, Jackie
Background: There has been significant attention paid in recent years to the economic costs of health service provision for people with palliative care needs. However, little is known about the costs incurred by family caregivers who typically provide the bulk of care for people at the end of life. Aim: To explore the nature and range of financial costs incurred by family caregiving within a palliative care context. Design: In-depth qualitative interviews were conducted with 30 family/whānau caregivers who were currently caring for someone with a life-limiting illness or had done so within the preceding year. Narrative analysis was used to identify impacts and costs at the personal, interpersonal, sociocultural and structural levels. Setting: Auckland, New Zealand. Findings: Costs of caregiving were significant and, for participants, resulted in debt or even bankruptcy. A range of direct (transport, food and medication) and indirect costs (related to employment, cultural needs and own health) were reported. A multi-level qualitative analysis revealed how costs operated at a number of levels (personal, interpersonal, sociocultural and structural). The palliative care context increased costs, as meeting needs were prioritised over cost. In addition, support from statutory service providers to access sources of financial support was limited. Conclusion: Families incur significant financial costs when caring for someone at the end of life. Research is now needed to quantify the financial contribution of family and whānau caregiving within a palliative care context, particularly given attempts in many countries to shift more palliative care provision into community settings.